Role of Health Programs Utilization and Social Factors on Adolescent Anemia Status - Arifah, Izzatul; Almayda, Mutiara Bahi; Widyani, Zahrina; Az Zahra, Qoonitah; Nuraisyah, Shinta Ramadhania; Werdani, Kusuma estu (Jurnal Kesehatan Masyarakat, 2025)
Adolescent-friendly Health Services (PKPR’s Nutrition service) are intended to eliminate adolescent malnutrition, including anemia. However, the effect of health program utilization on adolescent anemia has rarely been studied. This study intends to examine the prevalence of anemia, the relation of social and behavioral factors, and the use of PKPR’s nutrition service with the anemia status of adolescent girls in Surakarta. A school-based cross-sectional design was conducted at a senior high school in Surakarta. Samples were 275 female students in grades 10 and 11 who had experienced menstruation. Multiple regression analysis is deployed to model the factors associated with anemia. The prevalence of anemia in female students was 37.82%. The employment status of the father and mother is associated with the anemia status of adolescents. Other factors, such as parent education, family affluence scale, behavior factors, parent support, knowledge, attitude, perception, and self-efficacy, were not associated with anemia status. PKPR’s nutrition service utilization did not correlate with adolescents' anemia status. PKPR’s nutrition service has not yet had an impactful outcome in reducing the frequency of anemia. Further research is needed to evaluate its implementation and impact on adolescent health outcomes.